MicroRNA-34a induces transdifferentiation of glioma stem cells into vascular endothelial cells by targeting Notch pathway. Issue 10 (3rd October 2017) - Jin, Zaishun; Zhan, Tao; Tao, Jing; Xu, Biao; Zheng, Huizhe; Cheng, Yongxia; Yan, Bin; Wang, Hongwei; Lu, Guoqiang; Lin, Ying; Guo, Sufen
Abstract: The function of microRNA - 34a ( miR - 34a ) in transdifferentiation of glioma stem cells (GSCs) into vascular endothelial cells (VECs) was explored by focusing on Notch ligand Delta-like 1 (Dll1). MiR - 34a mimics was transfected into CD133 + glioma cell U251. The angiogenesis feature of miR - 34a transfected U251 cells was investigated and the expressions of CD31, CD34, Vwf, Notch 1, and Dll1 were quantified. Length of branching vessel-like structures in the miR - 34a transfected U251 cells was significantly higher than control cells. The VEC feature of miR - 34a overexpressed U251 cells was further confirmed by the expressions of CD31, CD34, and vWF. Transfection of miR - 34a decreased the expression of Notch 1 and Dll1. Furthermore, the miR - 34a overexpression-enhanced tube formation of GSCs was suppressed when the decreased expression of Dll1 was restored. The current study highlighted the potential of miR - 34a as an inducer in GSCs' transdifferentiation into VECs by targeting Dll1. Abstract: : Up-regulation of miR-34a induced transdifferentiation of CD133+ U251 cells into VECs